The Urgency Of Creating Regional Regulations For Supporting The Implementation Of Regional Autonomy - Lies Ariany; Risni Ristiawati (Syariah: Jurnal Hukum dan Pemikiran, 2019)
The Regional government which carried out based on the principle of autonomy as wide as possible implies that the regions are given the authority to regulate and manage all their own affairs. So, this study tried to conduct a study of normative law to further examine the nature of the implementation of regional autonomy, and the second tried to analyze the role of regional regulations in order to support the implementation of regional autonomy through library research using the statute approach and conceptual approach. The results of the study indicated that one of the important ideals and rationalities for implementing regional autonomy was to make the policy process closer to the society, not only in the central government. For this reason, authority needs to be given so that local governments can take their own initiative to make decisions regarding the interests of the local community through laws at the local government level. Thus, the contents of the Regional Regulations are to accommodate the interests of the people in the regions in order to achieve happiness and prosperity that is distributed equally to the people in the area.Pemerintah daerah dilaksanakan berdasarkan prinsip otonomi yaitu memberi dan melaksanakan rumah tangga itu sendiri. Untuk alasan ini, penelitian ini adalah studi hukum normatif untuk memeriksa lebih lanjut tentang pelaksanaan otonomi daerah dan pendekatan lain yang dapat dianalisis dengan menggunakan pendekatan perpustakaan menggunakan pendekatan Statuta dan pendekatan konseptual. Hasil penelitian menunjukkan bahwa salah satu cita-cita dan rasionalitas penting pelaksanaan otonomi daerah adalah membuat proses lebih dekat dengan masyarakat, tidak hanya di pemerintah pusat. Untuk alasan ini, perlu mengisi ruang sehingga pemerintah dapat mengambil inisiatif sendiri untuk membuat keputusan tentang lingkungan masyarakat melalui peraturan di tingkat pemerintah daerah. Ini adalah konten materi dari Peraturan Daerah pada dasarnya untuk mengakomodasi manfaat masyarakat di daerah dalam rangka mencapai kebahagiaan dan kemakmuran yang didistribusikan secara merata kepada orang-orang di daerah tersebut.(The regional government is carried out based on the principle of autonomy is giving and carrying out the household itself. For this reason, the research is normative legal studies to examine more about the implementation of regional autonomy and other approaches that can be analyzed using the library approach using the Statute approach and the conceptual approach. The results of the study show that one of the important ideals and rationalities of the implementation of regional autonomy is to make the process closer to the community, not only in the central government. For this reason, it is necessary to fill the space so that the government can take its own initiative to make decisions about the community environment through a regulation at the regional government level. This is the material content of the Regional Regulation is essentially to accommodate the benefits of the community in the area in order to achieve happiness and prosperity that is evenly distributed to the people in the area).